Long term oral azithromycin versus functional endoscopic sinus surgery in patients suffering from chronic rhinosinusitis: a comparative study - Yadav, Garima; Yadav, Mayank; Nautiyal, Deeksha; Anand, T. S. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Chronic rhinosinusitis (CRS) is defined as inflammation of the nasal cavity and paranasal sinuses. Azithromycin, a macrolide antibiotic, a well-established class of anti-bacterial agents, which also have anti-inflammatory properties. The present study was designed to compare the role of azithromycin with surgical management in patients with chronic-rhinosinusitis. Methods: The study population included 60 adult patients with symptomatic CRS refractory to 3 weeks of medical therapy. The patients were divided in two groups with 30 patients in each group. One group of patients received oral Azithromycin as main treatment for 12 weeks while the other group of patients underwent sinonasal surgery. Symptom scoring and endoscopic scoring were done previous to the treatment and at 1 month and 3-month follow-ups. Results: A good subjective as well as objective outcome in terms of symptom improvement was obtained with in patients with chronic rhinosinusitis with Surgical intervention as compared to those patients who received long term oral Azithromycin. Conclusions: We advocate that patients suffering from chronic sinonasal disease should be initially targeted with maximal medical therapy using an oral macrolide for at least 3 months. After this patient should be assessed and surgery considered in those cases refractory to medical therapy.